Advanced nano-graphite-infused salt-hydrated phase change materials derived from recycled waste for enhancing thermal energy storage with exceptional thermal stability - Yadav, Aman; Samykano, Mahendran; Pandey, Adarsh Kumar; Suraparaju, Subbarama Kousik; Natarajan, Sendhil Kumar; Ponnambalam, S. G. (Elsevier Ltd, 2025)
Thermal energy storage (TES) is a key technology for optimizing energy utilization by bridging the gap between supply and demand. Salt-hydrated phase change materials (SPCMs) have gained significant attention due to their high thermal conductivity and ability to enhance thermal effectiveness. However, SPCMs have low thermal stability and phase separation problems, which hinder their practical application. Hence, current research proposes an advanced SPCM composite incorporating synthesized battery waste particles as a cost-effective and efficient approach to overcoming these limitations. The battery waste particles were synthesized through a simple and effective method and subsequently integrated into the SPCM matrix via ultrasonication. Comprehensive thermal characterization was conducted to evaluate the suitability of the developed composite for TES applications. Experimental findings revealed that the composite exhibited a maximum thermal conductivity of 0.94 W/mK and a latent heat capacity of 88.67 J/g, signifying a 104.34 % improvement in thermal conductivity over conventional PCM. Long-term thermal stability was assessed through 500 charge–discharge cycles, confirming the material’s durability. Additionally, corrosion resistance tests demonstrated a lower corrosion rate than the base SPCM. These results indicate that battery waste-derived SPCM composites offer a promising solution for enhancing TES performance, stability, and longevity.